RETRACTED: Lactobacillus paracasei X11 Ameliorates Hyperuricemia and Modulates Gut Microbiota in Mice - Cao, Jiayuan; Liu, Qiqi; Hao, Haining; Bu, Yushan; Tian, Xiaoying; Wang, Ting; Yi, Huaxi (Frontiers in Immunology, 2022)
Hyperuricemia (HUA) is the presence of excessive uric acid (UA) in blood, which leads to an increased risk of chronic kidney disease and gout. Probiotics have the potential effect of alleviating HUA. The purpose of this study was to screen probiotics with UA-lowering activity and explore the underlying mechanism. The UA-lowering activity of 20 lactic acid bacteria strains was investigated in vitro and the effect of candidate probiotics on UA metabolism was evaluated using HUA Balb/c mice model. The results showed that Lactobacillus paracasei X11 had excellent UA-lowering activity in vitro, which could degrade nucleotides and nucleosides completely within 30 min, and the degradation rates of purine and trioxypurine could reach 83.25% and 80.42%, respectively. In addition, oral administration of L. paracasei X11 could reduce serum UA by 52.45% and inhibit renal proinflammatory cytokine IL-1β by 50.69%, regulate adenosine deaminase (ADA), xanthine oxidase (XOD) and transporter expression (GLUT9, NPT1, URAT1) to normal level. Moreover, it could restore the ratio of Bacteroidetes to Firmicutes (Bac/Firm Ratio) and showed a positive effect on the recovery of the intestinal microbiota. These findings provided fundamental information about the UA-lowering properties of probiotics, which suggested that L. paracasei X11 had the potential to be developed as novel probiotic strain to ameliorate HUA.